Current Opportunities and Trends in the Gas Sensor Market: A Focus on e-Noses and Their Applications in Food Industry - Selene Mor; Buse Gunay; Michele Zanotti; Michele Galvani; Stefania Pagliara; Luigi Sangaletti (Chemosensors)
Electronic noses (e-noses) are devices developed to recognize/classify odors and used in many fields, matching the current societal needs and concerns, such as food integrity and quality control, environmental monitoring, medical diagnostics, safety, and security in urban and industrial settlements. In this study, we review the application fields of e-noses based on a market analysis of currently available devices. A total of 44 companies active up to 2024, as well as 265 products, have been identified by considering the web pages of companies that feature e-noses among their products. These devices have been classified according to (i) the sensing mechanisms underlying the device performances and (ii) the application fields. The most diffused sensing devices/systems are chemiresistors (12.8%), electrochemical sensors (13.0%), catalytic beads (12.4%), and those based on optical detection techniques (16.0%). Commercial e-noses find large application in the industrial (21.0%) and chemical and petrochemical (21.0%) fields. A focus is made on the food and beverage application field, which is still a minor part of the overall share (6.0%) but is rapidly increasing and plays a relevant role in future applications where safety, sustainability, and quality issues are strictly intertwined. From this study, a rather complex picture emerges, and a proper taxonomy is expected to correctly classify the different kinds of e-noses.